2003
DOI: 10.1097/01.tp.0000083040.50727.ce
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor prevents chronic allograft dysfunction in liver-transplanted rats

Abstract: The findings indicate that dHGF may prevent chronic liver-allograft dysfunction and thus may become a novel treatment for chronic liver-allograft dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 27 publications
1
16
2
Order By: Relevance
“…In the context of liver transplantation, exogenous HGF administration to recipients of reduced-size liver graft enhances early restoration of liver volume, stimulates hepatic regeneration, and provides protection from rejection injury (1,(46)(47)(48). The results of the present study indicate that both ischemic preconditioning and NO donor treatments protect against hepatic I/R injury and improve hepatic regeneration in ROLT.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In the context of liver transplantation, exogenous HGF administration to recipients of reduced-size liver graft enhances early restoration of liver volume, stimulates hepatic regeneration, and provides protection from rejection injury (1,(46)(47)(48). The results of the present study indicate that both ischemic preconditioning and NO donor treatments protect against hepatic I/R injury and improve hepatic regeneration in ROLT.…”
Section: Discussionsupporting
confidence: 54%
“…Numerous investigations have demonstrated that HGF promotes hepatic growth and regeneration (1,13,15,16,(46)(47)(48). In the context of liver transplantation, exogenous HGF administration to recipients of reduced-size liver graft enhances early restoration of liver volume, stimulates hepatic regeneration, and provides protection from rejection injury (1,(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…23,24 However, it still remained uncertain whether tolerance could be induced by HGF in each model. In our study, administration of HGF could induce tolerance in the recipient, which was an unexpected but favorable effect on cardiac allografts.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have demonstrated that HGF is crucial in promoting liver regeneration following partial hepatectomy and transplantation in animal models [63][64][65][66][67] . HGF administration to recipients of reduced-size liver grafts in rats illustrated early regeneration and provided hepatoprotection against rejection-related injuries [64,68,69] . These essential signals are regulated by HGF, via c-met, the gene on the HGF-receptor.…”
Section: Growth Factors and Growth-factor Signaling Systems In Liver mentioning
confidence: 99%